POLYPHENOLS AS AN ANTIOXIDANT AGENT IMPROVES CHICKEN SPERM QUALITIES DURING COLD STORAGE - M. Gopi; P. V. Beulah; G. Prabakar; J. Mohan (Journal of Animal and Plant Sciences, 2020)
An in vitro study was carried out to assess the addition of polyphenols in the chicken seminal plasma on sperm quality and antioxidant status at different storage periods. Twenty healthy breeding roosters of White Leghorn chicken having similar body weight were randomly selected. The polyphenols in the pomegranate peels were extracted using methanol as a solvent. Samples were split equally into three portions for inclusion of different concentrations of 0, 50 and 100 ppm of polyphenols, respectively. Estimation of catalase, inhibition of lipid peroxidation, reduced glutathione and superoxide dismutase was done at 0, 24 and 48 h intervals. The sperm motility invariably increased in all treatment groups (50, 100 ppm) than control in both storage conditions. Other physical attributes such as sperm concentration, live and dead spermatozoa did not differ over control regardless of concentrations and time periods of storage. Inhibition of lipid peroxide action was found significant at the end of 48 h of storage in both the polyphenol treatment groups than control, while there was no change at 0 and 24 h. Polyphenols from pomegranate peels improved spermatozoal motility and antioxidant activity in seminal plasma and it could be concluded that the polyphenols has capability to protect the spermatozoa against oxidative damage.
Keywords: Pomegranate peels; phenols; white leghorn cocks; antioxidants; physical attributes